Pemberdayaan Anggota Ranting Aisyiyah Grendeng dalam Identifikasi Keamanan Jamu Tradisional Instan - Much Ilham Novalisa Aji Wibowo (Jurnal Pengabdian Pada Masyarakat, 2019)
EMPOWERMENT OF AISYIYAH BRANCH MEMBERS OF GRENDENG IN THE IDENTIFICATION OF INSTANT TRADITIONAL HERBAL MEDICINE SECURITY. Drug chemicals are still found in some instant powder herbal products even though BPOM has carried out its supervisory duties. The drug chemicals in instant herbal mixtures are selling points for unscrupulous manufacturers of traditional medicines because they offer an instant effect over claims of synthetic chemical drugs. The harmful effects of consuming traditional medicines containing medicinal chemicals are felt after 5 to 10 years later with the emergence of various disease conditions resulting from the addition of medicinal chemicals to herbal medicine. One effort to suppress the circulation of herbal medicine with drug chemical is to increase public knowledge in various ways. The activity is an effort to empower the community in identifying safe and legal Instant Traditional Herbal Medicine. Empowerment activities in this service activity are carried out in 5 stages with three main stages, namely the first lecture, which aims to increase public awareness and alertness about Jamu. The second activity is Group Teaching to add knowledge and information intensively in small groups. The third activity is Self Empowering in order to increase the independence of the community to solve the security problems of Traditional Herbal Medicine through training and peer teaching. The science and technology application program for the community can significantly improve partner knowledge based on the Paired T-test statistical test (P < 0.05). It can be concluded that after IbM activities, partners can choose excellent and right herbs based on the provisions of BPOM RI. Partners can distinguish herbal products, standardized herbal medicines, and phytopharmaca. Partners can find out how to use good and right herbs. Knowledge of partners after this activity increased significantly (P < 0.05) from the knowledge category to less good knowledge.